Aucuboside Inhibits the Generation of Th17 Cells in Mice Colitis - Chenxue Mei; Chenxue Mei; Xiao Wang; Fanxiang Meng; Xiaoqing Zhang; Ling Chen; Siqi Yan; Junxiu Xue; Xun Sun; Yuanyuan Wang (Frontiers Media S.A., 2021)
Aucuboside is an iridoid glycoside extracted from traditional Chinese medicine such as Rehmannia glutinosa, possessing a wide range of biological activities, including antioxidant, anti-aging, anti-inflammatory, and anti-fibrotic effects. The effects of aucuboside on inflammatory bowel disease (IBD) have not been studied. Therefore, the effects of aucuboside on the generation of Foxp3+ regulatory T (Treg) cells and IL-17-producing T helper (Th17) cells in colitis were studied. A mouse colitis model was established by intracolonic administration of 2,4,6-trinitrobenzene sulfonic acid (TNBS) to mimic human IBD. The generation of Treg and Th17 cells was evaluated by flow cytometry. Aucuboside significantly alleviated colitis symptoms, including weight loss, high disease activity index, and inflammatory responses. The generation of Th17 cells in colitis was significantly inhibited by aucuboside and accompanied by the suppression of IL-17 expression. In Raw264.7 cells, the LPS-induced increase in IL-17 expression was also suppressed by aucuboside, which was significantly blocked by the RORγt inhibitor sr2211. In addition, the decrease in the proportion of Treg cells was also partially reversed by aucuboside, which may reflect the aucuboside-induced inhibition of Th17 cells. This previously unrecognized immunoregulatory function of aucuboside may have clinical applications in IBD.